HUBUNGAN PERSEPSI KESERIUSAN PENYAKIT WANITA PASANGAN USIA SUBUR TENTANG INSPEKSI VISUAL ASAM ASETAT (IVA) DENGAN PEMERIKSAAN IVA UNTUK DETEKSI DINI KANKER SERVIKS DI DESA DURIN SIMBELANG KABUPATEN DELI SERDANG - Lindawati Simorangkir (STIKes Santa Elisabeth Medan, 2016)
Cervical cancer is a disease that ranked first cause of morbidity and mortality of women in Indonesia. In Durin Simbelang Village District Deli Serdang, from 100 women who tested with IVA as 2% positive for cervical cancer (higher than Glocoban International Agency Reasearch on Cancer estimates that is 0,016%). Early detection of cervical cancer can be done for free at the health center by using Visual Inspection with Acetate Acid (IVA) Goal: This study aims to determine the relationship perception of seriousness with the visual inspection with acetate acid test in Pancur batu. Methods The type of research was explanatory survey that aimed to analyze the relationship perception of seriousness on the visual inspection with acetate acid test. The population were 794 women of the reproductive age couples in Pancur Batu and the sample of 90 people were taken by simple random sampling technique. Data were analyzed using chi-square test on the level of 95%. Result: The results of research showed that variables which had relation with the visual inspection with acetate acid. Conclusion: Base on the result of research, it is suggested to IVA officer at the health centre to perform more intensive and continuous promotion about IVA by using methods and tools which easily understood by the women, and also coordinating with cadres and the leaders of religious meeting who could persuade women to do IVA test.